(untitled) (The Peerian Journal, 2024)
The article studies the efficacy of the drug Coraxan in the complex therapy of patients with coronary heart disease (CHD) and arterial hypertension (AH) in combination with chronic obstructive pulmonary disease (COPD). The use of Coraxan in the treatment of patients with combined cardiopulmonary pathology leads to a significant decrease in blood pressure (BP) and heart rate (HR), reduction of angina attacks. Coraxan increases tolerance to physical activity (PA).